- #1

Baela

- 17

- 2

Varying ##\partial_\lambda\phi\,\partial^\lambda\phi## wrt the metric tensor ##g_{\mu\nu}## in two different ways gives me different results. Obviously I'm doing something wrong. Where am I going wrong?

Method 1: \begin{equation}

(\delta g_{\mu\nu})\,\partial^\mu\phi\,\partial^\nu\phi

\end{equation}

Method 2: \begin{align}&\quad\,\, (\delta g^{\mu\nu})\,\partial_\mu\phi\,\partial_\nu\phi \nonumber \\

&=(-g^{\mu\rho}g^{\nu\sigma}\delta g_{\rho\sigma})\,\partial_\mu\phi\,\partial_\nu\phi \quad (\because \delta g^{\mu\nu}=-g^{\mu\rho}g^{\nu\sigma}\delta g_{\rho\sigma} \,\,\text{as can be checked by varying the identity}\,\, g^{\mu\lambda}g_{\lambda\nu}=\delta^\mu_\nu) \nonumber\\

&=-(\delta g_{\rho\sigma})\,\partial^\rho\phi\,\partial^\sigma\phi

\end{align}

The second result differs from the first one by a minus sign. What's going wrong?

Method 1: \begin{equation}

(\delta g_{\mu\nu})\,\partial^\mu\phi\,\partial^\nu\phi

\end{equation}

Method 2: \begin{align}&\quad\,\, (\delta g^{\mu\nu})\,\partial_\mu\phi\,\partial_\nu\phi \nonumber \\

&=(-g^{\mu\rho}g^{\nu\sigma}\delta g_{\rho\sigma})\,\partial_\mu\phi\,\partial_\nu\phi \quad (\because \delta g^{\mu\nu}=-g^{\mu\rho}g^{\nu\sigma}\delta g_{\rho\sigma} \,\,\text{as can be checked by varying the identity}\,\, g^{\mu\lambda}g_{\lambda\nu}=\delta^\mu_\nu) \nonumber\\

&=-(\delta g_{\rho\sigma})\,\partial^\rho\phi\,\partial^\sigma\phi

\end{align}

The second result differs from the first one by a minus sign. What's going wrong?

Last edited: